1270 nm near-infrared light as a novel vaccine adjuvant acts on mitochondrial photoreception in intradermal vaccines - Maki, Yohei; Kushibiki, Toshihiro; Sano, Tomoya; Ogawa, Takunori; Komai, Eri; Takahashi, Shusaku; Kitagami, Etsuko; Serizawa, Yusuke; Nagaoka, Ryosuke; Yokomizo, Shinya; Ono, Takeshi; Ishihara, Miya; et al. (Frontiers in Immunology, 2022)
With the development of laser technology in the 1960s, a technique was developed to inject intradermal vaccines immediately after irradiating the skin with laser light to elicit an adjuvant effect, referred to as “laser-adjuvant.” We have been investigating the mechanism of laser-adjuvant in influenza mouse models using noninvasive continuous-wave (CW) near-infrared (NIR) light mainly at a wavelength of 1064 nm, and have shown that the production of reactive-oxygen-species (ROS) in the skin and mast cells in the skin tissue plays an important role in the laser-adjuvant effect. The new wavelength of 1270 nm NIR-light is characterized by its ability to elicit the same vaccine adjuvant effect as other wavelengths at a lower energy, and may be suitable for clinical applications. In this study, we investigated the physiological activity of CW1270 nm NIR-light in mast cells, its biological activity on mouse skin, and the durability of the vaccine adjuvant effect in influenza vaccine mouse models. We show that irradiation of mast cells with 1270 nm NIR-light produced ROS and ATP, and irradiation of isolated mitochondria also produced ATP. In mouse skin, the relative expression levels of chemokine mRNAs, such as Ccl2 and Ccl20, were increased by irradiation with 1270 and 1064 nm NIR-light at minimum safe irradiance. However, the relative expression of Nfkb1 was increased at 1064 nm, but not at 1270 nm. Serum anti-influenza IgG antibody titers increased early after immunization with 1064 nm, whereas with 1270 nm, there was not only an early response of antibody production but also persistence of antibody titers over the medium- to long-term. Thus, to our knowledge, we show for the first time that 1270 nm NIR-light induces ROS and ATP production in mitochondria as photoreceptors, initiating a cascade of laser-adjuvant effects for intradermal vaccines. Additionally, we demonstrate that there are wavelength-specific variations in the mechanisms and effects of laser-adjuvants. In conclusion, CW1270 nm NIR-light is expected to be clinically applicable as a novel laser-adjuvant that is equivalent or superior to 1064 nm NIR-light, because it can be operated at low energy and has a wavelength-specific adjuvant effect with medium- to long-lasting antibody titer.